Catalytic Hydrogen Generation and Use for Production of Fuels - Bulushev, Dmitri A. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on catalytic hydrogen generation from formic acid, ammonia borane, and ethanol as well as on the production of fuels from tar using formic acid as a hydrogen source. The list of discussed catalysts includes single-atom catalysts, metallic/bimetallic catalysts, and supported metal complexes. These catalysts were thoroughly characterized using different methods. Optimized catalyst compositions are proposed.